IMPLEMENTASI PENGGUNAAN SISTEM INFORMASI AKUNTANSI UMKM DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Eny Tiara Rahmawati; Subagyo Subagyo; Dwi Budiadi (CAHAYA AKTIVA, 2019)
The presence of an Accounting Information System for Micro, Small, and Medium Enterprises (MSMEs) is one of the means to compile various reports that are indispensable for MSMEs to produce efficient and valid reports. The purpose of this research is to be able to find out the results of the implementation of an Accounting Information System in the era of the industrial revolution 4.0 on ikat weaving. This research only uses one respondent, namely AAM Putra Kota Kediri.This type of research conducted using case studies. In the method of data collection, this study uses interviews, observation, and documentation. Data analysis method used by the writer is descriptive analysis method with a qualitative approach.The results of data analysis and discussion of this study indicate that the aplication and readiness of the use of SIA is still not in line with the industrial revolution. Starting from recording the sales system and also the purchase. This study also shows the lack of employees or accounting department personnel in recording their books, due to lack of human resources and capital resources.Keywords: Accounting Information Systems, MSMEs, Industrial Revolution 4.0